Bed Use in the Intensive Care Unit During the Covid-19 Pandemic Era - Hesty Latifa Noor (Indonesian Journal of Global Health Research, 2021)
This study aims to compare the achievements of the Statistical Indicators in Intensive Care Units in hospitals between countries during the COVID-19 pandemic era. Specifically Analyzing the description of the Bed Occupancy Rate (BOR) in the Intensive Care Unit (ICU) Hospital during the Covid 19 pandemic era. This study carried out the preparation of a literature review with a systematic technique in selecting searches using international and national databases. Sources of data were obtained from journal searches using databases in journal applications. The library search technique uses keywords that match. Australia noted that the average BOR in the ICU of the Hospital was below the ideal standard of 27.4%, as well as what happened in Saudi Arabia, namely the BOR of the ICU room as much as 50%. Brazil and Canada in the ICU room BOR are at 80% and 80.5% which means they are still in the category of ideal standard values. In solo Indonsia, 98%, Yogyakarta Indonesia 82,72% and Surabaya Indonesia 99%. BOR in the ICU for patients with Covid 19 at the hospital is on average above the ideal standard of 75-85%. Australia noted that the average BOR in the ICU at the Hospital was below the ideal standard of 27.4% as was the case in Saudi Arabia, where the BOR in the ICU room was 50%. Brazil and Canada in the ICU room BOR are 80% and 80.5% and in Yogyakarta 82,72% which means they are still in the category of ideal standard values. The england recorded the BOR at 100% and solo and surabaya Indonesia in the second wave the increase in Covid-19 cases reached 98% and 99%. BOR in the ICU room above the ideal number results in a decrease in the quality of service in the ICU increases the percentage of deaths in the ICU and increases the risk of stress for medical staff.